Praktik Akad Sewa Tanah Untuk Produksi Bata Merah Tinjauan Hukum Ekonomi Syariah (Studi Kasus di Desa Tanjungsari Kec. Karangpawitan Kab. Garut) - Syaripudin, Enceng Iip; Setiawan, Ahmad (STAI Al Musaddadiyah Garut, 2022)
Islam regulates various aspects of human life (muamalah), including the practice of Lease Contracts for land. In conducting muamalah, Lease Contracts are often practiced among Muslim communities, yet there are still aspects that need improvement to align with Shariah principles. The formulation of the problem in this research is: How is the practice of land lease contracts used for red brick production in Tanjungsari Village, Karangpawitan Sub-District? What is the Shariah Economic Law perspective on the practice of land lease contracts for red brick production in Tanjungsari Village, Karangpawitan Sub-District? The objective of this research is to analyze the practice of land lease contracts in red brick production in Tanjungsari Village, Karangpawitan Sub-District, and to analyze the Shariah Economic Law perspective on the practice of land lease contracts in red brick production in Tanjungsari Village, Karangpawitan Sub-District. The research method used in this study is field research and a qualitative approach. The results of the research can be concluded as follows: the Shariah Economic Law perspective on the lease contract for red brick production in Tanjungsari Village meets the essential conditions of the lease contract. However, some conditions are not fulfilled, such as the lack of certainty regarding the end of the lease period. Therefore, according to Shariah Economic Law principles, the contract is not valid, making it invalid from a legal perspective. Keywords: Contract, lease, Shariah Economics.